Understanding the multidimensional linkages among renewable energy, pollution, economic growth and urbanization in contemporary economies: Quantitative assessments across different income countries' groups. (May 2021) - Armeanu, Daniel Stefan; Joldes, Camelia Catalina; Gherghina, Stefan Cristian; Andrei, Jean Vasile
Abstract: The objective of the present paper is to determine the existence of a link between energy, CO2 emissions, economic growth, and urbanization worldwide level. Therefore, to achieve our goal, we approached a series of statistical techniques that allow us to study the cointegration between variables, impulse response function to follows the effect of a shock that occurred, and not least we investigated the types of causality that are established through the Granger causality test. We selected annual data for the period of 1990–2014, for a number of 106 countries. The empirical results confirmed the presence of long-term associations. The impulse response functions and the variance decomposition gave us an overview on how the variables: renewable energy consumption, types of energy, economic growth, CO2, and urbanization are explained by the others variables. Following the Granger causality test, both unidirectional and bidirectional causal relationships were identified. We are confident that our empirical results should be of interest to researchers, regulatory institutions, and investors as well. Highlights: In case of upper middle-income countries a unidirectional relationship was found between the economic growths towards the variable employed. For low income nations, a bidirectional link was found among growth and energy intensity level of primary energy. We observe unidirectional relationships from CO2 emission to electric power consumption, age dependency ratio and unemployment. Our study used traditional unit root tests that do not check for presence of structural break tests.